Validation of the PROACTIVE Coping Inventory on Serbian University Students - Stanojević, Dragana Z.; Popović, Emilija U.; Dilparić, Branislava M. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The existing literature recognizes the importance of studying proactive coping among university students. There are two different conceptualizations of proactive coping, one by Aspinwall and Taylor (1997) and the other by Greenglass et al. (1999). To date, the Proactive Coping Inventory (Greenglass et al., 1999) is the most frequently used instrument that measures this concept. However, the main aim of the present study was to investigate the psychometric properties of a newly developed measure, the PROACTIVE coping inventory (Tian et al., 2023). The translation process of the PROACTIVE coping inventory followed the back-translation procedure. A series of questionnaires were completed online and a total of 171 respondents were included in the final sample. The age of the respondents ranged from 18 to 26; three quarters of them were female. Confirmatory factor analysis revealed that the Serbian version of the PROACTIVE coping inventory matched the original factor solution (χ2(df)= 202.350 (129), p= .000, χ2/df=1.569, CFI= .920, TLI= .908, RMSEA= .053). The active preparation, ineffective preparation, and self-management subscales showed good internal consistency (Cronbach α: .76, .73 and .73 respectively), while the utilization of social resources subscale had a lower but acceptable α= .66. The correlation analysis showed good convergent validity for all subscales except for ineffective preparation. The results obtained, the limitations of the study, and the need for future research have been discussed.